2019
DOI: 10.1108/ijppm-06-2019-0282
|View full text |Cite
|
Sign up to set email alerts
|

Prioritize the key parameters of Vietnamese coffee industries for sustainability

Abstract: Purpose The purpose of this paper is to identify the critical parameters of the Vietnam coffee industry and develop a comprehensive structural relationship to rank them for effective sustainable development. Design/methodology/approach The team of ten experts, having experience of over eight years in the field of various coffee industries in Vietnam, was created to give scores to multiple parameters. Technique for order of preference by similarity to ideal solution (TOPSIS) technique is used to develop the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 54 publications
0
41
0
1
Order By: Relevance
“…However, the positive outcomes in terms of increasing public reputation, improving financial indicators, and employee loyalty are specific benefits motivating local companies to take their CSR activities more seriously (Gonzalez-perez, 2015;Goyal and Kumar, 2017;Park et al, 2017). Nonetheless, the agricultural enterprises are excessively focused on economic benefits; meanwhile, lack of interest in technology development and quality management issues, as well as environmental protection issues, contribution to society, was the cause that made conditions for existing threats to their development (Do et al, 2020;Gonzalez-Perez and Gutierrez-Viana, 2012). Based on the vital role of TQM implementation and CSR initiatives, also the suggestions of prior studies in terms of examining the impact of TQM-enabling factors on the different performances, the purpose of this study proposes the theoretical framework and tests the hypotheses related to the relationship among TQM-enabling factors, CSR performance and business performance based on the agribusiness context of an emerging economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the positive outcomes in terms of increasing public reputation, improving financial indicators, and employee loyalty are specific benefits motivating local companies to take their CSR activities more seriously (Gonzalez-perez, 2015;Goyal and Kumar, 2017;Park et al, 2017). Nonetheless, the agricultural enterprises are excessively focused on economic benefits; meanwhile, lack of interest in technology development and quality management issues, as well as environmental protection issues, contribution to society, was the cause that made conditions for existing threats to their development (Do et al, 2020;Gonzalez-Perez and Gutierrez-Viana, 2012). Based on the vital role of TQM implementation and CSR initiatives, also the suggestions of prior studies in terms of examining the impact of TQM-enabling factors on the different performances, the purpose of this study proposes the theoretical framework and tests the hypotheses related to the relationship among TQM-enabling factors, CSR performance and business performance based on the agribusiness context of an emerging economy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the vital role of TQM implementation and CSR initiatives, also the suggestions of prior studies in terms of examining the impact of TQM-enabling factors on the different performances, the purpose of this study proposes the theoretical framework and tests the hypotheses related to the relationship among TQM-enabling factors, CSR performance and business performance based on the agribusiness context of an emerging economy. The author will perform hypothesis testing in the empirical context as the Vietnamese coffee firms, which have been one of the essential sectors that play a critical role of the Vietnam economy, the country considered as a transitional economy with gross national income (GNI) per capita in 2018 of approximately US$ 2,400 (Do et al, 2020;World Bank, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this method, an expert‐based method uses to give positioning the parameter with different experts' opinions (Wang and Lee (2009) and Singh et al (2016)). Do, Kumar, and Do (2019) proposed the TOPSIS model analysis to prioritize the key parameter of Vietnamese coffee industries for sustainability. In recent studies, Memari, Dargi, Jokar, Ahmad, and Rahim (2019), Lei, Wei, Gao, Wu, and Wei (2020), Chen (2019), Garg and Kumar (2020), Garg and Kaur (2020), Rani, Mishra, Rezaei, Liao, and Mardani (2020), and Liu and Wang (2020) have used TOPSIS method in their studies.…”
Section: Methodsmentioning
confidence: 99%
“…The carbon footprint result of 1-year average productivity showed that the conventional intensive (0.935 kg CO2e y la emergética (De Muner et al 2015;Giannetti et al 2011) para evaluar la sostenibilidad del cultivo de café. En segundo lugar, la dimensión más evaluada en cuanto a la sostenibilidad es la económica (5 artículos), las mismas se realizaron a partir de la aplicación de encuestas y entrevistas (Do et al 2019;Lingnau et al 2019)having experience of over eight years in the field of various coffee industries in Vietnam, was created to give scores to multiple parameters. Technique for order of preference by similarity to ideal solution (TOPSIS, análisis económico de costo beneficio (Anh et al, 2019;Villavicencio-Enríquez, 2012), y simulación a partir de costos asociados a certificación (Latynskiy & Berger, 2017).…”
Section: Extracción Y Síntesis De La Informaciónunclassified